The Effect of Drilling Routine Tasks on Students’ Vocabulary Mastery of Beginner English Class (BEC) at Islamic Boarding School Pamekasan - Ulul Laily,; Lasmi Febrianingrum, (PANYONARA: Journal of English Education, 2023)
Mastering vocabulary is the main modal to improve students' language proficiency. A limited vocabulary will obstruct them from mastering a language and its language skills. An English student must succeed in learning the language so they can get their English language proficiency. Drilling is still viable for increasing students' vocabulary knowledge, particularly for English beginners. To make the students enjoy in acquiring vocabulary, the drilling becomes a routine task done inside and outside the classroom. This investigation used an experimental research methodology with a one-group, pre-test, and post-test design. The research instruments used written test guidelines and documentation guidelines. While checking its validity, it is used Point Biserial Correlation formula. For its reliability, it is used KR-20. By contrasting the values of the t-test and t-table (7.863 > 2.093), the study's findings showed an increase in the students' vocabulary mastery after implementing drilling routine tasks. However, another kind of routine task by utilizing any media is recommended to be implemented.